Whole-genome sequence of Salmonella enterica subsp. enterica Serovar Typhimurium strain UPM 260, isolated from a broiler chicken in Perak, Malaysia - Roslan, Najwa Syahirah; Jabeen, Shagufta; Isa, Nurulfiza Mat; Omar, Abdul Rahman; Bejo, Mohd Hair; Ideris, Aini (American Society for Microbiology, 2017)
Salmonella enterica subsp. enterica serovar Typhimurium is one of several well-categorized Salmonella serotypes recognized globally. Here, we report the whole-genome sequence of S Typhimurium strain UPM 260, isolated from a broiler chicken.